Pemaknaan Karakter Semar dalam Perancangan Interior Co-Living sebagai Sarana Umum Untuk Menunjang Aktivitas Lansia - Friska Amalia; Mila Andria Savitri; Siti Chadijah (Jurnal PATRA, 2023)
Semar is a character from the punakawan story, he is a wise old brother as well as a humble character in the story. This research introduces and interpreted Semar as a symbol of life, hope, and future in the form of 3D visualization of an interior design for public space. Philosophically, Semar has a nurturing character that can relate to the interior of public spaces for the elderly. This research applies a grounded theory method as a qualitative approach to practice-led research by making experimental data on the interior design concept from Semar interpretation. Then observations were made and described in visual interpretation, resulting in an academic understanding of aesthetical elements and principles that is translated into interior design aspects. The results of the research consist of Semar interpretation in interior design 3D visualization, descriptive explanation of interior design concept from Semar interpretation as a symbol of life, hope, and future, and the process of creating interior design 3D models archives. All of this is expected as recommendations for ways to produce digital archives of interior design visualization of another Indonesian traditional culture.